The Role of the Village Government in Women's Empowerment Through Women Farmers' Groups (KWT) - Yulia Puji Lestarii; Siti Khumayah (Pelopor Publikasi Akademika, 2026)
Women Farmers' Groups (KWT) is an effort to encourage sustainable and equitable village development. This research examines the role of the Village Government in empowering women through KWT in Pajambon Village, Kramatmulya District, Kuningan Regency, West Java. The purpose of this study is to analyze the role of the Village Government in supporting the implementation of women’s empowerment activities through KWT. A qualitative descriptive research method was used, with data collected through interviews, direct observation, and documentation. The validity of the data was ensured through triangulation of sources and methods by comparing information obtained from interviews and field observations and by combining the results obtained. The aim was to obtain a more accurate picture and strengthen the data collected in the study. The results of this study indicate that the Village Government has successfully played a role as a facilitator and companion in empowering women through KWT. This study also recommends the need for training in marketing so that the products produced by KWT can become better known to the wider community.